Thinking of the development of housing policy - Ruonavaara Hannu (Routledge, 2022)
The Scandinavian (or Nordic) welfare model is world famous. It is known for its universal coverage of benefits and services, generous benefit levels, well-developed services – all financed with a relatively high progressive taxation that keeps income inequality rather small. Of course, the broad similarity is associated with a number of specific differences, and in recent decades all of the Nordic countries have moved away from the ideal typical Nordic model. In spite of the similarity of the welfare arrangements in the Nordic countries, their housing policies have never been similar. This difference of Nordic housing policies was the topic of a collaborative research project involving one researcher from each of the five Nordic countries: Denmark, Finland, Iceland, Norway and Sweden. The trajectory of housing policy in each country was analyzed with the help of an ideal typical periodization of housing policy, which seemed to apply to all countries investigated. In all of the countries four historical stages of the development of housing policies can be distinguished more or less clearly: (1) the introduction stage, (2) the construction stage, (3) the management stage and (4) the retrenchment or privatization stage. This paper presents the stage model used in the book and shows how it works in one case, that of Finland. The nature of the stage model is then scrutinized theoretically and empirically. Retrenchment is surely not the end of history of housing policy, so what after retrenchment? Are there elements of a cyclical model of policy development rather than a ‘linear’ periodization?  How to accommodate the actor-centered approach of the original project to the ‘structural’ periodization of the stage model? Is the change of housing policy structural or ideological?
International Housing Market Experience and Implications for China,